Integrating People of Terek Oblast into Socio-Cultural Space of Russia: Help of Charity (The Second Half of 19th – Early 20th Centuries) - Pokotilova, Tatyana Evgenevna; Rusetskiy, Mikhail Gennad`evich; Abdulaeva, Ilmira Abduragimovna (Journal of History Culture and Art Research, 2018)
The article is devoted to the entry of the peoples of the North Caucasus into the Russian socio-cultural space on the basis of the entry of the region into the Russian Empire. In the research the authors focus their attention on the issues of implementing such socio-cultural activity as charity within the mentioned process. Being traditional phenomena for worldview bases and cultural practices of the peoples of the North Caucasus that joined the Russian Empire and the peoples of the Russian Empire itself, encouragement for doing good and charity as such became significant factors contributing to peoples’ cultural rapprochement. This is confirmed by the analysis of specific historical data, facts of creating charity communities and diverse charity activities in Terek Oblast in particular, covering the second half of XIXth – early XXth centuries, that is presented in the article. At the same time the authors primarily consider the process of public care of the development of education in the region and the substitution of the efforts of the state that were organised into charity communities by society in the sphere of concern for socially disadvantaged groups of the region’s population.